Victimization of Sexual Minority Latinx Youth: Results From a National Survey. Issue 23 (December 2022) - Sabina, Chiara; Wills, Candence; Robles, Gabriel; Cuevas, Carlos A.
Limited previous research has explored the intersectional stress and trauma sexual minority (SM) Latinx youth experience generated by being part of at least two minoritized groups. The Dating Violence among Latino Adolescents (DAVILA) study employed a national sample of Latinx youth and queried a range of victimizations in the past year, via a bilingual phone survey. Of the 1525 12–18-year-old youth interviewed for DAVILA, 123 either identified as lesbian, gay, or bisexual or had at least one same-sex dating partner. Measures included the Juvenile Victimization Questionnaire, the Conflict Tactics Scale Short Form, Brief Symptom Inventory, and the Multidimensional Scale of Perceived Social Support. Rates of dating violence, psychological dating violence, sexual victimization, and polyvictimization were significantly higher among sexual minority (SM) youth, compared to heterosexual (HET) youth. Victimized SM youth had significantly more depression, anxiety, and hostility than victimized HET youth. Sexual minority youth also reported less social support from family and significant others. A sequential regression showed psychosocial factors of mental health functioning and social support were associated with the number of victimizations above and beyond demographic factors, including SM status. Together these results underscore that SM youth experience greater adverse outcomes than HET youth. However, it is not SM status that directly relates to victimization, but the negative effects of psychological distress and low social support, that account for the higher number of victimizations of SM Latinx youth. These factors are closely linked to the stigmatization that SM youth face. As such efforts to destigmatize SM identities are needed to address the health and safety of SM Latinx youth.